Complete genome analysis of Bacillus subtilis derived from yaks and its probiotic characteristics - Li, Aoyun; Wang, Meng; Zhang, Yu; Lin, Zhengrong; Xu, Mengen; Wang, Lei; Kulyar, Muhammad Fakhar-e-Alam; Li, Jiakui (Frontiers in Veterinary Science, 2023)
Probiotics have attracted increasing attention due to their multiple health benefits to the host. Yaks inhabiting the Tibetan plateau exhibit excellent disease resistance and tolerance, which may be associated with their inner probiotics. Currently, research on probiotics mainly focuses on their positive effects on the host, but information regarding their genome remains scarce. To reveal the potential functional genes of Bacillus subtilis isolated from yaks, we sequenced its whole genome. Results indicated that the genomic length of Bacillus subtilis was 866044638 bp, with 4,429 coding genes. The genome of this bacteria is composed of one chromosome and one plasmid with lengths of 4214774 bp and 54527 bp, respectively. Moreover, Bacillus subtilis contains 86 tRNAs, 27 rRNAs (9 16S_rRNA, 9 23S_rRNA and 9 5S_rRNA) and 114 other ncRNA. KEGG annotation indicated that most genes in Bacillus subtilis were associated with biosynthesis of amino acids, carbon metabolism, purine metabolism, pyrimidine metabolism and ABC transporters. GO annotation demonstrated that most genes in Bacillus subtilis were related to nucleic acid binding transcription factor activity, transporter activity, antioxidant activity and biological adhesion. EggNOG showed uncovered that most genes in Bacillus subtilis were related to energy production and conversion, amino acid transport and metabolism, carbohydrate transport and metabolism. CAZy annotation indicated that glycoside hydrolases (33.65%), glycosyl transferases (22.11%), polysaccharide lyases (3.84%), carbohydrate esterases (14.42%), auxiliary activities (3.36%) and carbohydrate-binding modules (22.59%) were found. In conclusion, this study first investigated the genome and genetic properties of Bacillus subtilis derived from yaks, which contributed to understanding the potential prebiotic mechanism of probiotics from the genetic perspective.